Hazardous characteristics of dust waste from metal manufacturing industries in South Korea. Issue 12 (December 2021) - Yoon, Cheol-Woo; Yoon, Young-Sam; Hong, Su-Yeon; Jeon, Tea-wan; Shin, Sun-Kyoung
The Ministry of Environment, South Korea, is involved in efforts to reduce safety-related accidents that could occur during hazardous waste disposal and minimise the environmental impacts of waste disposal. To reach such goals, new factors have been added that contribute to the hazardous characteristics of hazardous waste. The Ministry is also expanding regulations on inorganic and organic components present in hazardous waste for these factors and continues to correct the classification system to establish standards for waste components. Metallic dust, for example, is mostly generated during the operation of melting furnaces or precipitators and dangerous materials contained in this dust may cause accidents, such as explosions or fires. South Korean accident cases have confirmed that waste containing hazardous materials, such as Mg, Al and Mg–Al alloys, can cause such events. Therefore, this study analysed 28 dust samples collected from the dust accumulated in precipitators in 28 metal manufacturing facilities in South Korea. Nine samples were flammable and four samples were reactive to water. Two samples also exhibited leaching toxicities. The results applied to relevant laws in South Korea showed that the proportion of waste containing hazardous characteristics increased from 7.14% in the previous management category to 39.29% in the extended category, an overall increase of 32.15 percentage points.